Ameaça e caráter transnacional do narcotráfico na Amazônia brasileira - Aiala Colares Couto (Confins)
In this second decade of the 21st century, drug trafficking networks have weakened national defense policy on the frontiers, especially in the Amazon region, which places Brazil in a prominent position as a primary route of distribution of cocaine with Andean origin towards Europe and Africa, as well as, makes it a prominent consumer market for this drug occupying the second position in the world ranking. The aim of this article is to analyze the trans national character of drug trafficking in Brazilian Amazon, highlighting the existence of a geography crime based on regional-global connections that occur over the region. The research methodology used bibliographical and documentary analysis based on the or etical references that address the theme of drug trafficking and reports on drug seizure by the Federal Police and on UNODC (united nations office on drugs and crime) global crimes. Finally, field work was carried out in cities such as Belém, Cametá, Redenção, Marabá, Palmas and Santarém, where interviews and systematic observations were carried out. The results of thes cientific research point to the existence of a transnational dynamic of organized crime in the region that incorporates in its networks some strategic cities for the spatial organization of cocaine flows.